1996
DOI: 10.1159/000134452
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome homology between the domestic pig and the babirusa (family Suidae) elucidated with the use of porcine painting probes

Abstract: Homology among three pairs of domestic pig (Sus scrofa) and five pairs of babirusa (Babyrousa babyrussa) autosomes has been demonstrated with the use of porcine painting probes. With the results of this study, in addition to data obtained earlier through the application of banding techniques, correspondence between all individual chromosomes of these two distantly related pigs has been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
2
11
0
4
Order By: Relevance
“…The same inversion of SSC1p as in PPO14 can also be seen in the karyotype of B. babyrussa [Bosma et al, 1996;Thomsen et al, 1996]. The centric fusion SSC15/17 has been ascertained in B. babyrussa [Bosma et al, 1996;Thomsen et al, 1996], Phacochoerus aethiopicus [Bosma, 1978] and as polymorphic character in wild pig S. scrofa [Bosma, 1976].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The same inversion of SSC1p as in PPO14 can also be seen in the karyotype of B. babyrussa [Bosma et al, 1996;Thomsen et al, 1996]. The centric fusion SSC15/17 has been ascertained in B. babyrussa [Bosma et al, 1996;Thomsen et al, 1996], Phacochoerus aethiopicus [Bosma, 1978] and as polymorphic character in wild pig S. scrofa [Bosma, 1976].…”
Section: Discussionsupporting
confidence: 65%
“…However, there is a difference in fusion configuration among these chromosomes. While SSC13 and 16 are tandemly fused in acrocentric PPO13, the homologous submetacentric chromosomes in B. babyrussa [Bosma et al, 1996], P. aethiopicus [Bosma, 1978], P. africanus [this article] and S. cebifrons [O'Brien et al, 2006] originated from centric fusion of these chromosomes. In other words, PPO13 differs from homologous chromosomes in other Suidae by a pericentric inversion of the chromosomal segment equivalent to SSC16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pres ence of 18S+28S rRNA genes on babirusa chromosome 6 is unexpected. This chromosome cannot directly be matched to a specific domestic pig chromosome on the basis of banding pat terns, but recently it has been demonstrated that chromosomes 6 and 14 of the babirusa are together equivalent to chromo some 6 of the domestic pig (Thomsen et al, 1996;Bosma et al, 1996). Chromosome 6 of the domestic pig, however, does not contain 18S+28S rDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Originating from Northern Africa and Southeast Asia, wild boars are mammals of Artiodactyla order, Suidae family, represented by five genres, including the Sus (Bosma et al, 1996). The need to increase the productivity at wild boar farms has led to crossings between the wild boars and pigs.…”
Section: Introductionmentioning
confidence: 99%